JURNAL NASIONAL TEKNIK ELEKTRO DAN TEKNOLOGI INFORMASI: Pembangunan Class Library untuk Domain Product Management di Aplikasi M-Commerce pada Android - Adam Mukharil Bachtiar, Arifin Bardansyah (Teknik elektro UGM, 2017)
Criteo reports that the use of M-Commerce in 2015 has increased about 15% - 26%, compared to 2014. In 2015, users access M-Commerce using mobile phone more often than other devices. Around 54% of those users use mobile app while 46% use mobile browser. In addition, there is an increase in conversion value of the number of users switching from mobile browser to mobile app by 120%. In all these activities, 286% of users focus on product viewing activities. This phenomenon requires software developers to develop M-Commerce in a short time. On the other hand, the developers need time to develop MCommerce. One of the time-consuming activities is the development of functions for product management. Based on the software development, there is one concept that can be used, which is class library. A class library is a collection of classes and